A Review of Premenstrual Syndrome: Comparative Insights from Contemporary and Ayurvedic Perspectives - Dr. Anupriya,; Prof. (Dr.) Manjusha Karkare, (The Bioscan, 2026)
Introduction: Premenstrual Syndrome (PMS) is a common condition affecting women of reproductive age, characterized by a variety of physical, psychological, and behavioral symptoms occurring in the luteal phase of the menstrual cycle. The severity of PMS varies, with some women experiencing mild symptoms and others suffering from significant functional impairment. The management of PMS remains challenging, with both biomedical and Ayurvedic treatments offering different approaches to symptom alleviation.